Incidencia de la poda de mantenimiento en la rentabilidad del cultivo de cacao fino de aroma en el Cantón El Empalme Provincia del Guayas. - Coello Aguirre, Nelly Teresa (2015)
Investigating the impact of maintenance pruning crop profitability fine flavor cocoa was developed in the parish The Guayas of Canton, the results are expressed through some variables that highlight the most significant aspects. Regarding gender of farmers in the area, the result is placed in the (42%) male and (58%) female, ie the majority of farmers who practices pruned and resepa applied are women. Low productivity, poor management, severe attack of illness, advanced age cocoa orchards Campus Pineapples, leads to the need to implement rehabilitation technologies such as pruning and technical advice to be applied in traditional orchards cocoa farm producers. However, in general it can be said that the cost of production per hectare is around $ 250 and admission to a tech culture may reach $ 1,000 in a yield of 1360 kg / ha. In a semi tech culture, performance is reduced by half (680 kg / ha) and costs decrease by 20% especially in respect of fertilization. Performance-wise production of fine cocoa aroma pruning the graph 12 we can see that the 12 producers surveyed have a profitable crop production so having performed maintenance and completion pruning, much higher productivity. It is also observed in the graph 12, the revenue generated pruned cocoa, there was a significant increase revenues increased now, why producers are happy and grateful for having done pruning. Performance-wise production of fine cocoa flavor without pruning the graph 12 we can see that of the 12 respondents producers have a profitable crop production so having performed maintenance and completion pruning, it will increase its productivity. In the graph 13, the results of the revenue generated without pruning cocoa, of the 12 respondents producers are exposed, respondents have an income of $ 2565, a group of have an income of $ 2,025, while another group have a income of $ 1350, which shows that there was a large decrease in relation to income generated in cocoa. Estimates of production costs and van, tir analyze it with the investment of 1350 planting could implement the work of pruning in cocoa cultivation increasing production and profitability. Performance analysis of plantations with no pruning pruning and had a great difference to producers who apply pruning